Developing and validating a Japanese version of the Plymouth Sensory Imagery Questionnaire - Hitsuwari, Jimpei; Nomura, Michio (Frontiers in Psychology, 2023)
Mental imagery refers to the representation of stimuli that are not physically present and has long been a subject of interest in psychology. However, most research on mental imagery has been limited to visual images, with other types of imagery, such as sound and smell, receiving little attention. A possible reason for this is the lack of appropriate scales to measure the vividness of multisensory imagery. The Plymouth Sensory Imagery Scale (Psi-Q) has been developed to address this issue and has been used in several studies to measure the vividness of seven imageries: vision, sound, smell, taste, touch, body, and feeling. In this study of 400 participants in Japan, the Psi-Q was translated into Japanese and tested for reliability and validity. The results showed good internal reliability and retest reliability and moderate to high correlations with other measures of construct validity, including mindfulness, Big Five, and life satisfaction. Additionally, there is no significant difference in total Psi-Q scores between the Japanese and British samples, although some differences were found in individual sensory imagery abilities. This study provides valuable insights into multisensory mental imagery, and it is expected that research dealing simultaneously with the responses of multisensory modalities will further accumulate.